2022
DOI: 10.1093/ajcn/nqac082
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of child mortality reductions attributed to vitamin A supplementation in sub-Saharan Africa: scale up, scale back, or refocus?

Abstract: Background Vitamin A supplementation (VAS) has been implemented in over 82 countries globally, primarily because of its beneficial effect in preventing child mortality. Secular reductions in child mortality and the implementation of alternative programs to promote Vitamin A intake have led to questions on the need of national VAS programs. Objectives This study aimed to estimate child mortality changes related to VAS using cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…About a quarter of a billion children worldwide are estimated to have subclinical or clinically relevant low serum vitamin A levels, 6,7 with Vitamin A supplementation associated with reduce "all-cause mortality" and "all-cause morbidity". [385][386][387] Vitamin A is vital for normal vision, reproduction, and growth, for epithelial tissue integrity and immunity. 151,388 More severe forms of Vitamin A deficiency may manifest in clinical ocular signs such as night blindness and xerophthalmia.…”
Section: Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation
“…About a quarter of a billion children worldwide are estimated to have subclinical or clinically relevant low serum vitamin A levels, 6,7 with Vitamin A supplementation associated with reduce "all-cause mortality" and "all-cause morbidity". [385][386][387] Vitamin A is vital for normal vision, reproduction, and growth, for epithelial tissue integrity and immunity. 151,388 More severe forms of Vitamin A deficiency may manifest in clinical ocular signs such as night blindness and xerophthalmia.…”
Section: Vitamin Amentioning
confidence: 99%
“…About a quarter of a billion children worldwide are estimated to have subclinical or clinically relevant low serum vitamin A levels, 6,7 with Vitamin A supplementation associated with reduce “all‐cause mortality” and “all‐cause morbidity” 385–387 …”
Section: Vitamin Amentioning
confidence: 99%
“…a recent study by Baye et al 4 indicated that the estimated averted child deaths related to VA supplementation are highly variable among countries in the sub-Saharan African region. This can be partly explained by varying levels of all-cause mortality and VA supplementationamenable child morbidity and mortality.…”
Section: Bmj Nutrition Prevention and Healthmentioning
confidence: 99%
“…Every year, billions of VA capsules are distributed through the health system to reduce VA deficiency, reducing child morbidity and averting child death 2. However, with the increasing number of countries implementing interventions such as oil fortification and biofortification that can prevent VA deficiencies, continued VA supplementation is now primarily justified by its beneficial effect on reducing child morbidity and mortality3 4 Indeed, the anti-infectious vitamin was named after its immune-regulating function and beneficial effect in reducing diarrhoea and measles mortality 5…”
Section: Introductionmentioning
confidence: 99%
“…The scientific evidence from developing countries emphasised the beneficial effect of VAS on child survival.The recent meta-analysis by Baye et al reported that 100,000–230,000 child deaths would have been averted in sub-Saharan African (SSA) countries if the coverage of children with vitamin A supplementation (VAS) was 90% [ 11 ].…”
mentioning
confidence: 99%